Race, Place, Space, and Political Development: Japanese-American Radicalism in the “Pre-Movement” 1960s - Fujino, Diane C. (Social justice, 2008)
Part of a special issue on Asian and Pacific Islander populations within the U.S. The writer discusses several examples of Japanese-American radicalism in the years preceding the advent of the Asian-American Movement (AAM). She discusses U.S.-sanctioned concentration camps for Japanese-Americans during World War II and their radicalizing influence on the younger generation. She also comments on the influence of the black civil rights movement on Japanese-American activism, noting the part that proximity and geography played in this development. In particular, she looks at the lives and work of Japanese-American “pre-Movement” activists Yuri Kochiyama, Richard Aoki, and Mo Nishida.